New insights of growth hormone (GH) actions from tissue-specific GH receptor knockouts in mice - List, Edward O. (Arch Endocrinol Metab, 2019)
In order to provide new insights into the various activities of GH in specific tissues, recent advances have allowed for the generation of tissue-specific GHR knockout mice. To date, 21 distinct tissue-specific mouse lines have been created and reported in 28 publications. Targeted tissues include liver, muscle, fat, brain, bone, heart, intestine, macrophage, pancreatic beta cells, hematopoietic stem cells, and multi-tissue “global”. In this review, we provide a brief history and description of the 21 tissue-specific GHR knockout mouse lines. Arch Endocrinol Metab. 2019;63(6):557-67